PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DARI AIR LIMBAH CUCIAN BERAS DI DESA MUJUR, KABUPATEN LOMBOK TENGAH - Lestari, Putri Puji; Wulandari, Sagita; Fathony, Fami Rezha; Ramdani, Ari; Indrawan, Rama; Safar, Muhammad Attar Bensani; Saputri, Dhiyah Amalia; Hijraningsih, Selvia; Nanda, Meilita Rizkia Dwi; Sahira, Dian; Mulyati (Jurnal Wicara, 2024)
Mujur Village is a village located in East Praya District, Central Lombok Regency with a population of 8,103 people (BPS Central Lombok, 2024). The high population results in high demand for food such as rice, namely rice as a staple food. The process of processing rice into rice can produce waste which, if not used optimally, will cause an unpleasant odor. The aim of this training activity is to provide knowledge to the people of Mujur Village so that they can utilize waste rice washing water as POC. This activity was carried out on January 26 2024 at the Santong Hamlet Prayer Room, Mujur Village, East Praya District, Central Lombok Regency. The target participants or participants in this activity are 30 people consisting of housewives and farmer groups. This training activity method is carried out in two stages, namely outreach activities which are carried out with a series of material delivery using a lecture method about liquid organic fertilizer (POC) and assistance in making liquid organic fertilizer (POC) which is carried out to direct and involve participants in the practice of making liquid organic fertilizer ( POC) from rice washing waste. The community's response to this training activity was very enthusiastic. This is characterized by people being active in asking questions or being very responsive.